Upaya Kepala Madrasah Ibtidaiyah dalam Meningkatkan Kompetensi Profesional Guru di Desa Katapang - Dhiyaan Wadzikran; Asep Dudi Suhardini; masnipal (Bandung Conference Series: Islamic Education, 2024)
Abstract. A professional teacher is a guarantee of more effective teaching and learning implementation, and a qualified teacher is expected to be able to make the teaching and learning process successful to the maximum, from that it can create educational products that meet educational standards and follow the demands and needs of the community. The efforts made by the elementary madrasah in Katapang village are carried out by involving teachers in training and other development activities to improve the professional competence of teachers. The method used is a descriptive method with data collection techniques used are interviews and documentation. Data analysis techniques are carried out through several stages of data reduction, data presentation, and data verification. The results of this study are that the efforts of the elementary madrasah in Katapang village have participated in several trainings such as workshops, KKG, training, and supervision, but there are several obstacles in developing teacher professional competence seen from internal factors and external factors of the teacher. Abstrak. Guru yang profesional ialah jaminan pelaksanaan belajar mengajar yang lebih efektif, dan guru yang berkualitas diharapkan proses belajar mengajar dapat berhasil secara maksimal, dari itu dapat terciptanya produk pendidikan yang memenuhi standar pendidikan dan sesuai dengan tuntutan dan kebutuhan masyarakat. Upaya yang dilakukan madrasah ibtidaiyah di desa katapang di lakukan dengan mengikutsertakan guru dalam pelatihan dan kegiatan pengembangan yang lainnya untuk meningkatkan kompetensi profesional guru. Metode yang digunakan adalah metode dekriptif dengan teknik pengumpulan data yang digunakan adalah wawancara dan dokumentasi. Teknik analisis data dilakukan dengan melalui beberapa tahapan reduksi, penyajian data, dan verifikasi data. Hasil dari penelitian ini bahwa upaya madrasah ibtididaiyah di desa katapang sudah mengikuti beberapa pelatihan seperti workshop, KKG, diklat, dan supervisi, namun terdapat beberapa kendala dalam pengembangan kompetensi profesional guru dilihat dari faktor internal dan faktor eksternal guru tersebut.